Comparison of formant scores between complete denture users and subjects with complete dentition: a preliminary study - Andryas, Ika; Syarfina, Tengku; Tanti, Ira; Kusdhany, Lindawati S.; Hong, Guang (Padjadjaran Journal of Dentistry, 2025)
Introduction: Edentulism impairs the ability to chew, eat, and speak properly. Dentures, which aim to address this issue, are also believed to contribute to a decrease in the peak intensity value and spectral width of sound formants. Formants refer to the air within the vocal tract that is set in vibration by the vocal fold's action. This study aims to observe changes in formant values between complete denture users and participants with complete dentition. Methods: This preliminary study recruited six voluntary participants, divided into two groups. The first group consisted of subjects with complete dentition, while the second group comprised individuals wearing complete dentures on both arches. All participants introduced themselves, and their speech was recorded using PRAAT® software. For the second group, recordings were made both with and without dentures. Statistical analysis was performed using one-way ANOVA. Results: Significant differences in formant scores were observed across all groups. Post hoc tests revealed a significant difference in formant scores between completely edentulous subjects without dentures and the complete dentition group; Conclusion: Correcting speech defects is the third main objective in fabricating denture prostheses. Enhancing the phonetically beneficial construction of denture quality improves psychosocial parameters, including quality of life and socialization abilities, and accelerates successful Prosthodontic treatment. The findings indicate that the format score of a person with a complete denture is not substantially different from that of an individual with complete dentition. Conversely, individuals who have lost their complete dentures and not using complete denture may exhibit significant differences in formant score.